Non-steroidal anti-inflammatory drugs and gabapentinoids for chronic lumbar pain: a Bayesian network meta-analysis of randomized controlled trials. Issue 1 (21st April 2021) - Migliorini, Filippo; Maffulli, Nicola; Eschweiler, Jörg; Tingart, Markus; Baroncini, Alice
Abstract: Introduction: Several pharmacological therapies have been proposed for the management of chronic low back pain (LBP), but no consensus has been reached yet. Source of data: Recent published literatures identified accessing PubMed, Google scholar, Embase and Scopus. Areas of agreement: Exploring effective conservative alternatives to the surgical intervention is of especial interest. Areas of controversy: The efficacy and safety of non-steroidal anti-inflammatory drugs and gabapentinoids for chronic LBP are debated. Several clinical studies showed controversial results, and the most effective and safe class of drugs has not yet been clarified. Growing points: The effects of selective and non-selective NSAIDs and gabapentinoids in chronic LBP are probably over-estimated. Areas timely for developing research: The effect of behavioural changes, including exercise, should be explored, alone or in combination with drugs.